Review artikel: Potensi Tanaman Nilam (Pogostemon cablin Benth.) Sebagai Agen Antikanker: Article review : Potential of the Patchouli (Pogostemon cablin Benth.) as an Anticancer Agent - Wulandari, Ayu; Fristiohady, Adryan; Wahyuni, Wahyuni; Sahidin, Sahidin; Arba, Muhammad; Irnawati, Irnawati (Jurusan Farmasi Poltekkes kemenkes Makassar, 2025)
Globally, cancer remains one of the leading causes of death, and the number of cases continues to increase along with world population growth, population aging and modern lifestyles. The prevalence of cancer in 2024 will still be influenced by many factors, including lifestyle, diet, environmental exposure, and advances in cancer detection and treatment. Currently, a lot of research related to alternative cancer therapy focuses on the use of natural product as anticancer agents that are more selective, effective, and with lower side effects. This article review aims to provide information regarding the patchouli plant (Pogostemon cablin) and its potential as an anticancer agent. This review was carried out by collecting literature from various databases published in the last 10 years (2014 – 2024). Based on literature searches, P. cablin is known to have anticancer activity against endometrial, ovarian, liver, skin, nasopharyngeal, prostate, blood, colorectal and lung cancer.